Putative virulence factors of extra-intestinal Escherichia coli isolated from bovine mastitis with different clinical scores - Guerra, S. T. [UNESP]; Dalanezi, F. M. [UNESP]; de Paula, C. L. [UNESP]; Hernandes, R. T. [UNESP]; Pantoja, J. C.F. [UNESP]; Listoni, F. J.P. [UNESP]; Langoni, H. [UNESP]; Ribeiro, M. G. [UNESP] (Oxford University Press (OUP), 2019)
We investigated the genes kpsMTII, iucD, sfaDE, afaBC, papA and papC, (proposed to be involved in extra-intestinal pathogenic Escherichia coli—ExPEC), phylogroup classification and the in vitro swimming and swarming motility in 50 E. coli isolated from bovine mastitis with different clinical severity scores (mild, moderate and severe). The aforementioned genes were detected in 12 (n = 12/50; 24·0%) isolates. kpsMTII and iucD were the most frequent genes identified in six (n = 6/50; 12·0%) and four (n = 4/50; 8·0%) of the isolates, respectively. In only one (n = 1/50; 2·0%) isolate, more than one gene was simultaneously identified: iucD and kpsMTll were detected whereas sfaDE and afaBC were not detected. Mild, moderate and severe clinical signs were observed in 40·0% (n = 20/50), 28·0% (n = 14/50) and 32·0% (n = 16/50) of the cases. Commensal phylogroups B1 (n = 19/50; 38·0%) and A (n = 19/50; 38·0%) were prevalent; whereas pathogenic phylogroups B2 and D were observed in only 10·0% (n = 5/50). Swarming and swimming motilities were observed in 90·0% (n = 45/50) and 68·0% (n = 34/50) of the isolates, respectively; and there was a significant association (P = 0·0036) between swarming motility and severe clinical cases (score 3). To the best of our knowledge, this is the first study where clinical severity of bovine mastitis cases and the genes proposed to classify ExPEC were assessed in relation to swarming and swimming motility. Significance and Impact of the Study: Escherichia coli is classified as extra-intestinal (ExPEC) when strains contain at least two of the genes kpsMTII, iucD, sfaDE, afaBC and papA and/or papC. We investigated in vitro motility and the presence of these genes in 50 E. coli isolated from bovine mastitis with different clinical scores (mild, moderate and severe). Clinical severity was not associated with the genes studied. Swarming motility was associated with severe cases (score 3) of clinical mastitis. Results of this study contribute to a better understanding of the factors that determine the severity of clinical mastitis.
Keywords: coliform mastitis; ExPEC; mastitis; swarming and swimming motility; virulence mechanisms